Anticoagulant-administered pulmonary embolism in post-cholecystectomy: choosing the lesser of the two evils - Haroon, Raihanah; Abu Bakar, Intan Bazilah; Shaharuddin, Nur Adilah; Ahmad, Azrin Waheedy (2022)
Introduction: Anticoagulant or blood thinning agents are well-established as the first line for pulmonary embolism treatment. It is vital in order to prevent the existing clot from enlarging and new clots from forming. It is known to increase the risk of bleeding, however not many cases have been reported to cause liver injury or hematoma. Case: We present a case of an 82-year-old male who underwent cholecystectomy for ruptured gallbladder empyema. Post-operative, he was complicated with multiple intra-abdominal collections and perihepatic infected hematoma. He also developed segmental pulmonary embolism which required anticoagulant. The dilemma occurred when he became hypotensive and dropping hemoglobin levels with repeated CT angiogram revealed new subcapsular hematoma with liver lacerations. Conclusion: Even though anti-coagulants rarely cause spontaneous liver hemorrhage, a thorough risk-benefit assessment needs to be performed in patients who underwent liver-related surgery since both liver haemorrhage and pulmonary embolism carries mortality risk to the patient. This is important to balance the need to prevent traumatic or possible spontaneous liver haemorrhage with the demand to treat the on-going pulmonary embolism.